CLINICAL OUTCOMES OF RETROPERITONEAL LAPAROSCOPIC URETEROLITHOTOMY FOR UPPER URETERAL STONES AT NGHE AN FRIENDSHIP GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and evaluate the outcomes of retroperitoneal laparoscopic ureterolithotomy for upper ureteral stones at Nghe An Friendship General Hospital.Methods: A study was conducted on 54 patients diagnosed with upper third ureteral stones who underwent retroperitoneoscopic surgery at the Department of Urology, Nghe An Friendship General Hospital from June 2025 to December 2025.Results: The mean age of patients was 50.7 ± 11.3 years. The most common presenting symptom was dull flank pain (72.2%). The mean stone size was 16.6 ± 3.4 mm (range: 10–24 mm). The mean operative time was 68.3 ± 8.2 minutes (range: 42–102 minutes). The mean postoperative hospital stay was 4.1 ± 0.9 days (range: 3–8 days). The rate of good outcomes was 98.1%.Conclusion: Retroperitoneal laparoscopic ureterolithotomy is a safe and effective technique for treating upper ureteral stones, providing a high stone clearance rate, low complication rate, and short hospital stay.
Keywords: Upper ureteral stone; Retroperitoneal laparoscopic ureterolithotomy.